SIMULATION OF FUZZY LOGIC CONTROLLER AS DIRECTION ADJUSTMENT FOR LINE FOLLOWING ROBOT - Diva, Imelda Putri (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Line Follower is a robot that follows a line, and in it there is an Integrated Circuit that contains programming to run it. In this experiment, the line follower using fuzzy logic control provides another alternative in the control system. In fuzzy logic control, there is no need for a mathematical model of the system because fuzzy logic control works based on rules. The designed control is a one input, two output system and uses the Mamdani system as an inference mechanism. The output error in the program will increase when the robot turns to follow the trajectory, the error can occur due to the calculation of the membership function input and rules as a determinant of robot action when detecting the trajectory in front of it. Therefore, in this line follower experiment, the rule will be a reference in processing the input value of the distance and speed of the right and left motors, the rule also determines the direction of the robot using the help of a camera sensor.